2009
DOI: 10.1111/j.1349-7006.2009.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining kallistatin gene therapy and meloxicam to treat hepatocellular carcinoma in mice

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancerrelated causes of death, and conventional treatments offer unsatisfactory response. We have previously reported that kallistatin gene therapy suppressed the growth of HCC tumors by its antiangiogenic activity, and meloxicam, a selective COX-2 inhibitor, inhibited proliferation and induced apoptosis of human HCC cells in vitro. The aim of this study was to determine whether combining kallistatin gene therapy and meloxicam could offer a better therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Several studies have shown that NSAIDs, Coxibs and aspirin help to prevent cancer 56 . In particular, the effect of meloxicam has been described as inhibiting primary tumor growth in hepatocellular carcinoma or ovarian cancer mouse models 57,58 , as well as having an anti-metastatic effect in an orthotopic osteosarcoma mouse model 59 .…”
Section: Side Effects Of Nsaids and Coxibsmentioning
confidence: 99%
“…Several studies have shown that NSAIDs, Coxibs and aspirin help to prevent cancer 56 . In particular, the effect of meloxicam has been described as inhibiting primary tumor growth in hepatocellular carcinoma or ovarian cancer mouse models 57,58 , as well as having an anti-metastatic effect in an orthotopic osteosarcoma mouse model 59 .…”
Section: Side Effects Of Nsaids and Coxibsmentioning
confidence: 99%
“…Kallistatin is an effective inhibitor of angiogenesis and inflammation. In murine models of tumor xenografts, kallistatin treatment inhibits the development of diverse cancers, including breast, liver, colon, lung and gastric carcinoma [2934, 47]. Moreover, systemic delivery of the kallistatin gene dramatically inhibits experimental lung metastasis, inflammation and angiogenesis in tumor-bearing mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…Kallistatin possesses anti-tumor activity as evidenced by inhibiting tumor growth and metastasis in animal models [2934, 47]. For example, intramural injection of adenovirus carrying the human kallistatin gene into pre-established breast cancer xenografts in nude mice results in significant suppression of tumor growth and reduction of blood vessel numbers [29].…”
Section: Kallistatin Retards Tumor Growth and Metastasis In Tumor-mentioning
confidence: 99%
See 1 more Smart Citation
“…41 While there are no published reports of the effects of meloxicam on clinical or preclinical in vivo OSCC studies, Meloxicam has been shown to induce tumor cell apoptosis in human patients with esophageal cancer 42 and reduce tumor growth in animal models of other forms of cancer including osteosarcoma, 43 hepatocellular carcinoma 44 and ovarian carcinoma. 45 …”
Section: Discussionmentioning
confidence: 99%